Pengaruh Kualitas Produk, Harga, dan Promosi Terhadap Keputusan Pembelian Powder Drink Pada Jakarta Powder Supply (JPS) Cabang Banyuwangi - Tutut Hariyadi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
Competition in the current era of globalization requires marketers to always develop and seize market share. Marketing activities will achieve good results, so producers must know in advance what the needs and desires of consumers are, so that the products offered will be in accordance with market conditions. This quantitative study aims to analyze and test the effect of product quality, price and promotion on purchasing decisions using simple random sampling technique with 85 respondents (buyers) of powder drink at JPS (Jakarta Powder Supply) Banyuwangi Branch. The data collection technique used a questionnaire.